Utilization of Cockle Shell (Anadara Granosa) as Partial Replacement of Fine Aggregates in Concrete - Rachman, Ranno Marlany; Soeparyanto, Try Sugiyarto; Ngii, Edward (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2021)
This research aimed to utilize Anadara Granosa (Blood clam shell) clamshell waste as a new innovation in concrete technology and to investigate the effect of Anadara Granosa clamshell powder utilization as an aggregate substitution on the concrete compressive strength. The sample size was made of cylinders with a size of 10 cm x 20 cm with variations of clamshell powder 10%, 20% and 30% from the fine aggregate volume then soaked for 28 days as per the method of the Indonesian National Standard. The evaluation results exhibited that the slump value exceeded the slump value of normal concrete with a slump value of 0% = 160 mm, 10% = 165 mm, 20% = 180 mm and 30% = 180 mm. Additionally, it was found that the concrete compressive strength obtained post 28 days were 20.78 Mpa, 21.95 Mpa, 21.17 Mpa and 24.28 Mpa for normal concrete (0%), substitution concrete (10%), substitution concrete (20%) and substitution concrete (30%), respectively. Leading on from these results, it was concluded that the increment of Anadara Granosa clamshell powder substitution led to the increase of concrete compressive strength test.